Association between depression and enterovirus infection: A nationwide population-based cohort study. Issue 5 (February 2017) - Liao, Yin-To; Hsieh, Ming-Hong; Yang, Yao-Hsu; Wang, Ying-Ching; Tsai, Ching-Shu; Chen, Vincent Chin-Hung; Gossop, Michael
Abstract : Abstract: Enterovirus (EV) infection is common among children and adolescents. Few studies have investigated the relationship of depression after EV infection. This study explores an association between EV infection and subsequent depression in children and adolescents and assesses the risk of depression after EV infection with central nervous system involvement in a nationwide population-based retrospective cohort. A random sample of 1, 000, 000 people was derived from Taiwan National Health Insurance Research Database and we identified enrollees less than 18 years with EV infection before 2005 and followed up until December 2009. A total 48, 010 cases with EV infection and 48, 010 healthy controls matched for sex, age, and residence were obtained. Association between EV infection and depression risk was assessed by Cox proportional hazards models to determine the hazard ratios (HRs) and confidence intervals (CIs). We further stratified EV infection into with central nervous system (CNS) involvement and without and compared with matched cohort. Children and adolescents with EV infection had no elevated risk of depression compared with healthy controls (adjusted HR, aHR = 1.00, 95% CI: 0.83–1.21). However, CNS EV infection was associated with increased risk of depression (aHR = 1.62, 95% CI: 1.02–2.58) in the fully adjusted Cox regression model. To the best of our knowledge, this is the first study investigating depression in children and adolescents with CNS EV infection. The results suggested that children and adolescents with CNS EV infection were a susceptible group for subsequent depressive disorders. Abstract : Supplemental Digital Content is available in the text